Letter : Spanish Civil War - Elvin, Herbert Henry
010-0136-001 NATIONAL UNION of CLERKS & ADMINISTRATIVE WORKERS. TRADE UNION No. 916. APPROVED SOCIETY No. 184 TELEPHONE NO.: HOLBORN 1733 TELEGRAMS : "UNICLERKOS. PHONE. LONDON." REGISTERED OFFICE : 17-20, Holborn Hall Gray's Inn Road London, W.C.1. WHEN REPLYING PLEASE QUOTE : Your Ref.: Our Ref. : 80/1/4. Sir Walter Citrine, TRADES UNION CONGRESS GENERAL COUNCIL, Transport House, SMITH SQUARE, S.w.1. All communications to be addressed to The General Secretary. Write a separate letter for each subject dealt with. 14th August, 1936. Dear Sir Walter, SPANISH CIVIL WAR. Like all of us I have been exercised about the developments in Spain, and this has been intensified by the news about the supply of war material to the rebels appearing in the papers this morning. I know the excuse given that our Government (and, I suppose, other Governments too) take up the line that they cannot ban the selling of civil machines but I look upon this simply as an excuse. The difficulty is accentuated by the fact that Parliament is not sitting. I have no doubt that you have been keeping in touch with things, but I wondered if the Finance & General Purposes Committee have met to consider what action if any can be taken, e.g., what about a deputation to the Prime Minister and the Foreign Secretary? Is not the supply of war material - direct or indirect - of any kind to the rebels an "act of war" against Spain? If so, should not action be taken against those supplying such material under the League Covenant? If, by chance, a meeting of the Committee referred to has not been called, I think it would save the General Council from undue criticism if it could be said that it had met, had considered the situation, and was keeping in close touch with developments so as to take prompt action if necessary. Yours fraternally, Herbert H. Elvin GENERAL SECRETARY. 292/946/10/149